N170 reflects orthographic uniqueness point effects in English among native Japanese and Korean readers. (19th January 2021) - Yum, Yen Na; Law, Sam-Po
Highlights: Native English readers showed orthographic uniqueness point effects at the N170. More negative N170 was elicited by words with early orthographic uniqueness point. N170 latency or lateralization was not affected by orthographic uniqueness point. Non-native readers of typologically different first scripts showed similar patterns. Results are consistent with a parallel letter processing account. Abstract: Orthographic uniqueness point (OUP) refers to the letter position of a word at which it is distinguishable from other lexical items in the language. Previous findings of OUP effects have been mixed and mainly demonstrated in native readers of alphabetic languages. The current study investigated whether OUP effects could be shown among non-native readers in a visual repetition detection task. The experiment tested three OUP conditions (early, mid, late) in native English readers and proficient non-native English readers whose native scripts were Japanese or Korean. Results revealed main effects of OUP on N170 amplitude, where early OUP words elicited more negative N170 and late OUP words elicited marginally less negative N170 than mean activation for both native and non-native readers. There was no indication that non-linearity or non-alphabetic nature of one's native script influenced OUP effects. Results were consistent with a parallel letter processing account in single word reading.